The fertility timing gap: the intended and real timing of childbirth - Slabá, Jitka; Kocourková, Jiřina; Šťastná, Anna (Journal of biosocial science, 2024)
The fertility gap, which indicates the difference between the planned and actual number of children born, can be explained by the shift in parenthood to older ages and is associated with the non-attainment of one's intended reproductive plans. This paper focuses on the gap in the timing of entry into parenthood, i.e. between the planned and actual age at the birth of the first child. The study is based on data from the Women 2016 survey which re-interviewed women of fertile age from the second wave of the Czech Generations & Gender Survey conducted in 2008. At the population level, the fertility timing gap differs across generations. While for Czech women born between 1966 and 1971 the planned age exceeded the actual observed age by one year, the realisation of fertility occurred two years later than planned for the youngest generation (1983-1990) included in the study. At the individual level, the later-than-planned realisation of fertility was found to be related primarily to partner-related factors.
Keywords: populační dynamika; Population Dynamics; Child; lidé; Female; fertilita; Infant; zdravotnické služby; Pregnancy; Fertility; dítě; těhotenství; kojenec; Health Services; ženské pohlaví; Humans